Let's break down the given steps in solving the equation \(2x + b = c\):
-
Original Equation:
\(2x + b = c\) -
Step 1:
\(2x + b - b = c - b\)
This step is correct as it simplifies to \(2x = c - b\). -
Step 2:
\(2x = c - b\)
This step is also correct. -
Step 3:
The given step states \(2x - 2 = c - b - 2\).
This step is incorrect. It should rather have stayed as \(2x = c - b\). -
Step 4:
\(x = \frac{c - b - 2}{2}\) (if we were to try to get to this step from an incorrect step).
However, since Step 3 contains an error, Step 4 can't be computed correctly based on erroneous information.
Conclusion:
- There is no error in the process until Step 2.
- The error occurs from Step 2 to Step 3.
- Consequently, Step 4 is also based on this incorrectness.
Valid Conclusions:
- There is no error in the process. (False)
- The process has an error from step 1 to step 2. (False)
- The process has an error from step 2 to step 3. (True)
- The process has an error from step 3 to step 4. (True)
Therefore, the true statements are:
- The process has an error from step 2 to step 3.
- The process has an error from step 3 to step 4.